2011
DOI: 10.1016/j.biomaterials.2010.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of the dual release of stromal cell-derived factor-1 and bone morphogenetic protein-2 from hydrogels on bone regeneration

Abstract: The objective of this study is to evaluate the activity of gelatin hydrogels incorporating combined stromal cell-derived factor-1 (SDF-1) and bone morphogenetic protein-2 (BMP-2) on the in vivo bone regeneration at an ulna critical-sized defect and subcutaneous site of rats, and compared with that of those incorporating either SDF-1 or BMP-2. The similar release profile of SDF-1 and BMP-2 from the hydrogels was observed with or without the combination of BMP-2 and SDF-1, respectively. An enhanced bone regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 60 publications
4
100
1
Order By: Relevance
“…AMD3100, a bicyclam antagonist of CXCR4, was initially developed for selective inhibition of CXCR4-facilitated human immunodeficiency virus (HIV) entry into cells, 47 and later it was reported to mobilize hematopoietic stem cells by directly antagonizing the CXCR4-mediated sensing of the SDF-1 chemotactic gradient in bone marrow. 48 Our data demonstrate, for the first time, that SDF-1b plays a pivotal role in suboptimal BMP-2-induced bone formation and maturation through regulating CXCR4 signaling in vivo, extending previous reports [26][27][28][29] and confirming our earlier findings in vitro.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…AMD3100, a bicyclam antagonist of CXCR4, was initially developed for selective inhibition of CXCR4-facilitated human immunodeficiency virus (HIV) entry into cells, 47 and later it was reported to mobilize hematopoietic stem cells by directly antagonizing the CXCR4-mediated sensing of the SDF-1 chemotactic gradient in bone marrow. 48 Our data demonstrate, for the first time, that SDF-1b plays a pivotal role in suboptimal BMP-2-induced bone formation and maturation through regulating CXCR4 signaling in vivo, extending previous reports [26][27][28][29] and confirming our earlier findings in vitro.…”
Section: Discussionsupporting
confidence: 80%
“…38 Previous studies have suggested that the CXCR4/SDF-1 signaling axis regulates BMP-2 osteoinduction in vitro 24,25 and in vivo. [21][22][23][26][27][28][29] However, clear distinctions between involved SDF-1 isoforms were not reported. Thus, the specific contribution of SDF-1b, the second most abundant splice variant, to BMP-2-induced bone formation remained unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GMP containing constructs were implanted subcutaneously in mice for 6 weeks to investigate whether bone formation can be induced in cell-free constructs by chemokine attraction of host MSCs or if bone formation can be enhanced in seeded constructs due to a synergistic BMP-2/SDF-1α combination 67 . Transfection of seeded MSCs with BMP-2 plasmid DNA is possible in alginate constructs.…”
Section: Resultsmentioning
confidence: 99%
“…The recruitment of MSCs towards BMP-2 protein or genetically engineered BMP-2 producing MSCs, via SDF-1α or -β induces osteogenic differentiation 224 . When both growth factors are released from a combined construct, a synergistic effect on bone formation has even been reported 67 . The mechanism behind this increased bone formation has been described as a combination of enhanced mobilization and homing of bone marrow-derived osteoprogenitor cells to the implant leading to increased numbers of cells available for bone regeneration at ectopic bone implants 66 .…”
Section: Introductionmentioning
confidence: 99%